Potassium permanganate (KMnO4)/sodium sulfite (Na2SO3) rapidly disintegrates waste activated sludge by reactive Mn(III) species and shapes microbial community structure - Li, Wei; Lou, Yu; Fang, Anran; Feng, Kun; Xing, Defeng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •KMnO4 + NaSO3 co-treatment rapidly disintegrates waste activated sludge in 10 s.•Secondary pollution of soluble manganese was almost all eliminated.•KMnO4 + NaSO3 co-treatment with in-situ generated reactive Mn(III) species.•KMnO4 + NaSO3 co-treatment has a great impact on the microbial community.•Anerolineae, Clostridia, and Deltaproteobacteria exhibited positive correlation with WAS hydrolysis and anaerobic digestion. Using potassium permanganate (KMnO4) as a reagent to pretreat waste activated sludge (WAS) is subject to limitations owing to high cost for large-scale facilities, as well as secondary manganese pollution. Permanganate/bisulfate (PM/BS) processes have been effectively used to eliminate pollutants from water treatment. However, this technology as an advanced oxidation process for pretreating WAS is relatively unexplored. In the present study, we investigated an adjustable permanganate/sulfate (with KMnO4 and Na2SO3) method to enhance disintegrable performance with in situ-generated reactive Mn(III) species. The results showed that this method could degrade WAS at extremely fast speed (10 s). The concentration of SCOD and VFAs of the KMnO4 + Na2SO3 co-treated WAS notably increased, up to 3125 mg/L and 2276 mg/L, respectively, by 10 s. KMnO4 + Na2SO3 co-treatment could enhance the sludge floc disintegration, release proteins and polysaccharides to soluble EPS fraction, and promote nutrient release. Phosphorus release by the KMnO4 + Na2SO3 co-treatment reached 4498.3 mg/L, which was 3-fold higher than that obtained by the KMnO4 pretreatment. No surplus soluble manganese was found with this method during the operation. Additionally, Illumina HiSeq sequencing of 16S rRNA gene amplicons showed that microbial diversity decreased after KMnO4 + Na2SO3 co-treatment. The predominant phyla of treated sludges belonged to Bacteroidetes, Proteobacteria, Firmicutes, and Chloroflexi. Anerolineae, Clostridia, and Deltaproteobacteria had a positive correlation with WAS hydrolysis and anaerobic digestion. Archaeal communities were not distinct in all sludge samples, and predominant populations were affiliated with Methanothrix and Methanobacterium. This study describes a rapid and efficient process for enhancing WAS degradability and shaping microbial communities with the KMnO4 + Na2SO3 co-treatment.